Sistem Informasi Penjualan Bahan Jahit Baju dan Celana di Toko MJ Textile Kotapinang Berbasis Web - Aditya, Faisal (Journal of Computer Science and Information System(JCoInS), 2022)
Information Systems Sales and Purchase of Goods is a system that provides information services in the form of data sales and purchases of goods and stock items. The existence of this information system is very important. In this case the store MJ TEXTILE used as a place of research, as the information system of sales and purchases of goods on the site have not been managed well so often goes wrong in making the report, such as data processing sales transactions, data processing purchase, processing goods data, customer data processing, and data processing supplier members. The purpose of this study is to provide convenience at the time of data processing goods, customers and suppliers, simplify the data processing sales and purchases, minimize errors in the data recording purchases and sales data. To overcome these problems, we need a web-based system as one solution for optimizing the use of computers to the processing of data by designing an information system that is applied to the PHP programming language and MySQL database in order to solve the existing problems and respond to the needs of the company.